Impact of Mobile based Messages through KVKs in Haryana - Kumari, Saroj; Sethi, Nishi; Malik, Joginder Singh (Indian Journal of Extension Education, 2018)
The information and communication technologies like radio, TV, newspapers, telephones and magazines are playing a  major role in sustainable agricultural development since early decades and now the modern ICTs as mobiles and  computers and have created a revolution. Kisan mobile advisory service (KMAS) was launched for sending agricultural  information through Short Message Service (SMS). The present study was undertaken to assess the impact of message in  terms of information input, process and output delivered through mobile based advisory services (MBASs) by KVKs.  Out of all, 12 Krishi Vigyan Kendras (KVKs) used mobile based advisory services (MBASs). Among them , two KVKs - Fatehabad and Sirsa were randomly selected for the assessment of impact. Out of that list, 150 registered farmers were  selected randomly from each KVK, comprising total sample of 300 registered farmers. The overall information output  pattern of the mobile based messages as received by registered farmers was found to be medium (61.00%) followed by  high (23.67%) and low (15.33%) information output pattern.
Keywords: Impact; information; KVK; messages; mobile based advisory service; SMS